Interferon gamma as an immune modulating adjunct therapy for invasive mucormycosis after severe burn – A case report - Tawfik, Dina M.; Dereux, Caroline; Tremblay, Jan-Alexis; Boibieux, Andre; Braye, Fabienne; Cazauran, Jean-Baptiste; Rabodonirina, Meja; Cerrato, Elisabeth; Guichard, Audrey; Venet, Fabienne; Monneret, Guillaume; Payen, Didier; et al. (Frontiers in Immunology, 2022)
Background Mucormycosis is a deadly fungal infection that mainly affects severely immunocompromised patients. We report herein the case of a previously immunocompetent adult woman who developed invasive cutaneous mucormycosis after severe burn injuries. Interferon-gamma (IFN-γ) treatment was added after failure of conventional treatment and confirmation of a sustained profound immunodepression. The diagnosis was based on a reduced expression of HLA-DR on monocytes (mHLA-DR), NK lymphopenia and a high proportion of immature neutrophils. The immune-related alterations were longitudinally monitored using panels of immune-related biomarkers. Results Initiation of IFN-γ was associated with a rapid clinical improvement and a subsequent healing of mucormycosis infection, with no residual fungi at the surgical wound repair. The serial immunological assessment showed sharp improvements of immune parameters: a rapid recovery of mHLA-DR and of transcriptomic markers for T-cell proliferation. The patient survived and was later discharged from the ICU. Conclusion The treatment with recombinant IFN-γ participated to the resolution of a progressively invasive mucormycosis infection, with rapid improvement in immune parameters. In the era of precision medicine in the ICU, availability of comprehensive immune monitoring tools could help guiding management of refractory infections and provide rationale for immune stimulation strategies in these high risk patients.